Usefulness of Grey Scale and Doppler transvaginal sonography in diagnosis of ovarian torsion (Journal of Fatima Jinnah Medical University, 2020)
Background: Ovarian torsion diagnosis is a great challenge as delay in diagnosis can cause severe morbidity. Early accurate diagnosis is crucial to preserve ovarian function. Ultrasonography being the primary imaging modality plays a vital role in the evaluation of suspected ovarian torsion by helping surgeons reach the correct diagnosis, thus avoiding unnecessary intervention. This study aims to determine the diagnostic accuracy of isolated and combined sonographic features of ovarian torsion on grey scale and Doppler transvaginal ultrasonography.Patients and methods: From radiology database, from January 2016 till December 2019, sonographic signs of ovarian torsion in 113 women with suspected ovarian torsion on ultrasonography and subsequent surgical diagnosis were evaluated. Ultrasound findings were compared with surgical findings to determine the accuracy, sensitivity, specificity, and positive and negative predictive values of individual and combined ultrasound signs.Results: Diagnostic accuracy of ultrasound for ovarian torsion was 85.8%. Abnormal ovarian Doppler flow was the most accurate individual sonographic sign with accuracy, sensitivity, specificity and positive predictive value of 85.8%, 83.5%, 100% and 100% respectively followed by ovarian enlargement and ovarian edema. Combined ultrasound signs resulted in higher sensitivity and positive predictive values, and lower specificity and negative predictive values for ovarian torsion. Increasing the number of sonographic parameters increased the specificity but decreased sensitivity. High accuracy, sensitivity, positive predictive value, specificity and negative predictive value was seen when combination of three or two sonographic parameters was used as diagnostic criteria.Conclusion: Transvaginal sonography is a convenient, reliable and extremely useful imaging modality for preoperative diagnosis of ovarian torsion with high specificity, sensitivity, positive predictive value and diagnostic accuracy helping treating physicians to take prompt decisions regarding timely surgical intervention. However, due to low negative predictive values, absence of sonographic signs does not rule out ovarian torsion and high index of clinical suspicion remains of utmost importance.
Keywords: Ultrasonography; Ovarian torsion; Accuracy